Critical Perspectives to Advance Educational Equity and Health Justice. Issue 4 (2022) - Cannon, Yael; Tuchinda, Nicole
Abstract: A robust body of research supports the centrality of K-12 education to health and well-being. Critical perspectives, particularly Critical Race Theory (CRT) and Dis/ability Critical Race Studies (DisCrit), can deepen and widen health justice's exploration of how and why a range of educational inequities drive health disparities. The CRT approaches of counternarrative storytelling, race consciousness, intersectionality, and praxis can help scholars, researchers, policymakers, and advocates understand the disparate negative health impacts of education law and policy on students of color, students with disabilities, and those with intersecting identities. Critical perspectives focus upon and strengthen the necessary exploration of how structural racism, ableism, and other systemic barriers manifest in education and drive health disparities so that these barriers can be removed.